Achieving margin clearance following oncoplastic breast surgery in comparison with simple wide local excision: a three‐dimensional specimen assessment. Issue 11 (17th August 2020) - Garreffa, Emanuele; Kankam, Hadyn K. N.; Bali, Radhika; Duckworth, Adam; Jimenez Linan, Mercedes; Mahler Araujo, Betania; Moyle, Penelope; Wright, Penny; Provenzano, Elena; Agrawal, Amit
Abstract : In this paper, we reviewed the three‐dimensional interplay between tumour and surgical specimen dimensions in patients undergoing oncoplastic breast surgery compared to simple wide local excision. The relationship between tumour and specimen medio‐lateral, supero‐inferior and antero‐posterior dimensions were explored in both groups. Despite larger tumour dimensions, oncoplastic surgery is not inferior to wide local excision in providing clear surgical margins. Abstract: Background: Pre‐operative breast tumour radial dimensions often determine the choice between simple wide local excision (WLE) and oncoplastic breast surgery (OBS). We reviewed the three‐dimensional interplay between tumour and surgical specimen dimensions in the two cohorts. Methods: Demographic, tumour and treatment data were collected for all patients undergoing OBS by a single surgeon and compared with a randomly selected cohort of WLE patients treated. The relationship between tumour and specimen medio‐lateral, supero‐inferior and antero‐posterior dimensions were explored in both groups. Subgroup analyses were performed in the OBS cohort (parenchymal displacement versus replacement). Results: We identified 60 OBS patients (63 breasts), comparing them with 60 WLE patients. Pre‐operative tumour estimated size was significantly larger in the OBS cohort and concordant with macroscopic tumour radial dimensions and final microscopic tumour size. Surgical specimen weight was more than 3.5 times higher in the OBS group and its radial dimensions were almost double. No significant difference was observed for the antero‐posterior dimensions. The rate of margin re‐excisions and completion mastectomies were lower in the OBS cohort. WLE patients with positive margins had a lower tumour‐to‐specimen ratio, whereas, the requirement for further surgery in the OBS cohort was associated with larger tumour dimensions. Conclusion: Despite larger tumour dimensions, OBS is not inferior to WLE in providing clear surgical margins. Our analysis of the three‐dimensional spatial relationship between cancer and surgical specimen, although not completely conclusive, can be helpful in the selection of the most appropriate surgical approach for every patient.